2009
DOI: 10.1007/s00217-009-1115-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nucleic acid lateral flow immunoassay for simultaneous detection of Listeria spp. and Listeria monocytogenes in food

Abstract: We present a new nucleic acid lateral flow immunoassay (NALFIA) for the assessment of listeria contamination. The detection procedure starts with enrichment of sample in Half Fraser broth (24 h). Following isolation of DNA, a duplex PCR is performed with two labelled primer sets, one generic and directed to a specific sequence of the gene encoding 16S rRNA from Listeria spp. and the other specific and directed to a part of the prfA gene encoding the central virulence gene regulator from the food pathogen Liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 25 publications
0
26
1
Order By: Relevance
“…S5). The detection limit reported in this study which is 1 pg of genomic DNA is lower than that of a LAMP-NALFIA reported by Nimitphak et al (2008) (1 ng), a PCR-NALFIA by Blazkova et al (2009) (50 pg) and a LAMP-NALFIA by Kaewphinit et al (2013) (5 pg) whereas a PCR-NALFIA developed by Soo et al (2006) reported a similar LOD of 10 CFU/ml. An amplification-free NALFIA assay described by Pohlmann et al (2014) reported a higher detection limit of 10 4 CFU/ml.…”
Section: Optimisation Of Dry-reagent-based Late-pcr-nalf Assaycontrasting
confidence: 78%
“…S5). The detection limit reported in this study which is 1 pg of genomic DNA is lower than that of a LAMP-NALFIA reported by Nimitphak et al (2008) (1 ng), a PCR-NALFIA by Blazkova et al (2009) (50 pg) and a LAMP-NALFIA by Kaewphinit et al (2013) (5 pg) whereas a PCR-NALFIA developed by Soo et al (2006) reported a similar LOD of 10 CFU/ml. An amplification-free NALFIA assay described by Pohlmann et al (2014) reported a higher detection limit of 10 4 CFU/ml.…”
Section: Optimisation Of Dry-reagent-based Late-pcr-nalf Assaycontrasting
confidence: 78%
“…In addition, borate buffer (containing both H 3 BO 3 and Na 2 B 4 O 7 ) was previously reported to have superior performance for lateral flow immunoassays that adopt a hapten-antibody detection system. (9)(10)(11) We thus compared a boric buffer (H 3 BO 3 ) with a borate buffer (Na 2 B 4 O 7 ), in the presence of 1% BSA as the blocking molecule. We also compared these buffers with the standard immunoassay buffers TBS-T and TENTC.…”
Section: Buffer Studymentioning
confidence: 99%
“…: A set of primers specific for L. monocytogenes was used to amplify a part (274 bp) of the prfA gene encoding the central virulence gene regulator as described (Blazkova et al 2009). One of these primers was 5'-tagged with DIG and the other with biotin.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…In this one-step format, the labelled amplicons were mixed with the conjugate of neutravidin and carbon nanoparticles in incubation buffer, immediately applied and detected after one to several hours. Such mixed immuno-DNA formats have been used in lateral flow and microfluidic detection assays (Baeumner 2004;Blazkova et al 2009;Blazkova et al 2011;Corstjens et al 2001;Koets et al 2009;Kozwich et al 2000;Mens et al 2008;Noguera et al 2011;van Amerongen & Koets 2005;Wang et al 2006). To get proof of concept for the use of carbon nanoparticles as signal labels in antibody microarrays we studied two applications in which the antigens consisted of double-tagged DNA amplicons: the detection of L. monocytogenes and the detection of three antibiotic resistance genes from Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%